2004
DOI: 10.1111/j.1365-2621.2004.tb10711.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High‐Pressure Pretreatment and Calcium Soaking on the Texture Degradation Kinetics of Carrots during Thermal Processing

Abstract: Carrots (Daucus carota) pretreated under different high-pressure conditions were thermally processed at temperatures in the range of 90°C to 110°C. Texture degradation (hardness) was monitored objectively using a texture analyzer. For a given thermal treatment, the rate constant (k-value) decreased with increasing pretreatment pressure. A high-pressure pretreatment (200 to 500 MPa) at 60°C for 15 min resulted in a more pronounced texture improvement compared with the same pretreatment at 20°C and 40°C, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 32 publications
3
60
0
Order By: Relevance
“…This strengthening effect of the middle lamella matrix is often deliberately pursued through controlled stimulation of endogenous PME activity, for example, by means of a mild temperature or hydrostatic pressure pretreatment, prior to the actual conservation process. [171][172][173] Supplementing these pretreatments by calcium soaking further increases the firmness improvement. 172 In cases where a (thermal) pretreatment would activate detrimental enzymes or where only low amounts of endogenous PME are present, application of exogenous PME through enzyme infusion can be performed (e.g., the commercial preparation NovoShape from Novozymes).…”
Section: Pme In Relation To Texture Of Plant-based Foodsmentioning
confidence: 94%
See 1 more Smart Citation
“…This strengthening effect of the middle lamella matrix is often deliberately pursued through controlled stimulation of endogenous PME activity, for example, by means of a mild temperature or hydrostatic pressure pretreatment, prior to the actual conservation process. [171][172][173] Supplementing these pretreatments by calcium soaking further increases the firmness improvement. 172 In cases where a (thermal) pretreatment would activate detrimental enzymes or where only low amounts of endogenous PME are present, application of exogenous PME through enzyme infusion can be performed (e.g., the commercial preparation NovoShape from Novozymes).…”
Section: Pme In Relation To Texture Of Plant-based Foodsmentioning
confidence: 94%
“…[171][172][173] Supplementing these pretreatments by calcium soaking further increases the firmness improvement. 172 In cases where a (thermal) pretreatment would activate detrimental enzymes or where only low amounts of endogenous PME are present, application of exogenous PME through enzyme infusion can be performed (e.g., the commercial preparation NovoShape from Novozymes). [174][175][176] Formation of calcium-pectin crosslinks may also improve or preserve the viscosity of liquid plant-based products.…”
Section: Pme In Relation To Texture Of Plant-based Foodsmentioning
confidence: 94%
“…The enzyme was extracted 24,25 from the pellets using 0.2 mol L −1 Tris buffer, pH 8 with 1 mol L −1 NaCl for 2 h (1:2 w/v). The suspension was centrifuged at 10 000 × g for 1 h. The supernatant was subjected to ammonium sulfate precipitation.…”
Section: Extraction Of Apple Pectin Methylesterasementioning
confidence: 99%
“…Measurement of pectin methylesterase activity PME activity was determined by measuring the release of acid per time unit 24 at pH 7.0 and 63…”
Section: Extraction Of Apple Pectin Methylesterasementioning
confidence: 99%
“…The application of high pressure pretreatment was described to increase the water and solute diffusion during osmotic dehydration of pineapples, potato, glutinous rice and turkey breast [26][27][28][29]. Sila et al, [30] demonstrated that combined effect of high pressure treatment and CaCl 2 treatment improved the texture of carrots during thermal processing. High pressure-assisted infusion of pectin methyl esterase and calcium chloride in strawberry was shown to improve the firmness [13,31].…”
Section: Introductionmentioning
confidence: 99%